Acute surgical disease in COVID19 patients - Lončar, Zlatibor; Micic, Dusan; Petrovic, Natasa; Laban, Marija; Perisic, Zlatko; Milenkovic, Marija; Gregoric, Pavle (Halo 194 Scientific Journal of Emergency Medicine, 2020)
The aim of this paper is to review current publishing papers on COVID-19 to provide essential suggestions on how to manage the acute surgical problems during the pandemic. A systematic review was conducted of the most relevant articles published between 30 December 2019 and 30 April 2020. Access to the operating theatre is almost exclusively restricted to emergencies and oncological procedures. The use of laparoscopy ishould be cautiously considered, as the main risk lies in the presence of the virus in the pneumoperitoneum . All efforts should be deployed in order to evaluate the feasibility of postponing surgery until the patient is no longer considered potentially infectious or at risk of perioperative complications. If surgery is deemed necessary, the emergency surgeon must minimise the risk of exposure to the virus by involving a minimal number of healthcare staff .  In case of the pandemic circumstances, open surgery should be considered.
Keywords: Emergency surgery, Pandemic, Covid-19, organization, surgical triage, surgical procedures